Pemilihan food outlet sebagai faktor risiko berat badan lebih anak usia sekolah dasar di Kecamatan Tegalsari Surabaya - Renny Evelyn Hartono; BJ. Istiti Kandarina; Siti Helmyati (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTIntroduction: Overweight and obesity are conditions resulting from an imbalance of calories in the body that occur in a long time and cause more deaths than underweight. One of factors related is food pattern, which also infl uenced the selection of food outlets. Surabaya is an urban area so it has many types and characteristic s of food outlet. Elementary school (4, 5, 6) do not really depend on their parents, so their food consumption and physical activity began to vary. Objectives: To identify the relationship between the selection of food outlets and overweight/obesity status of elementary school in Tegalsari district, Surabaya.Methods: This research used a case-control study design. Samples were 51 children for each group of cases and control and obtained from 11 primary school in the 5 subdistricts in Tegalsari district, Surabaya. Data were obtained by interview, direct observation of food outlets, and interview to select informants about the reasons of selecting food outlets . Quantitative data were processed by bivariate (chi-square) and multivariate (binomial regression) test. Results: Bivariate test results showed that there were signifi cant relationships between the frequency to the street vendors consumption (OR=4.09, 95% CI:1.60-10.75), frequency of fast food consumption (OR=2.86, 95% CI:1.19-6.94) and snacks (OR=6,05, 95% CI:2.20-17.62), physical activity (OR=3.09, 95% CI:1.28-7.51) and gender (OR=2.70, 95% CI:1.11-6.64) with overweight/obesity status, while frequency of stores (total, supermarket, market, mini-market), frequency of food service place (total, restaurants, fast food restaurants), frequency of vegetable and fruit consumption, and socio-economic status of respondents did not relate signifi cantly. In multivariate analysis, the variables that affected frequency of the street vendors were snack consumption, physical activity, sex and total expenditure. Conclusions: Frequency of the street vendors, fast food consumption, physical activity,gender, and total expenditure had relationship with overweight/obesity status.KEYWORDS: food outlet, obesity, overweightABSTRAKLatar belakang: Overweight dan obesitas adalah keadaan akibat ketidakseimbangan kalori dalam tubuh yang terjadi dalam waktu lama dan menjadi penyebab kematian lebih banyak dibanding underweight. Salah satu faktor yang berhubungan langsung adalah pola makan, yang juga dipengaruhi pemilihan food outlet. Surabaya merupakan daerah perkotaan sehingga memiliki jenis dan karakteristik food oulet lebih beragam. Anak usia SD kelas IV, V, VI sudah tidak terlalu bergantung pada orang tua, sehingga konsumsi pangan dan aktivitas fisiknya mulai beragam. Tujuan: Mengetahui hubungan antara pemilihan food outlet dan status berat badan lebih pada anak usia sekolah dasar di Kecamatan Tegalsari, Surabaya.Metode: Penelitian menggunakan desain studi kasus-kontrol. Sampel penelitian adalah 51 anak untuk masing-masing kelompok kasus dan kontrol dari 11 SD di 5 Kelurahan di Kecamatan Tegalsari, Surabaya. Data diperoleh dengan wawancara, observasi langsung ke food outlet dan wawancara alasan pemilihan food outlet pada informan terpilih. Data kuantitatif diolah dengan uji bivariat (chi-square) dan multivariariat (regresi binomial).Hasil: Uji bivariat menyatakan terdapat hubungan signifi kan antara frekuensi datang ke pedagang kaki lima (OR=4,09, 95% CI:1,60-10,75), frekuensi konsumsi fast food (OR=2,86, 95% CI:1,19-6,94) dan kudapan (OR=6,05, 95% CI:2,20-17,62), aktivitas fi sik (OR=3,09, 95% CI:1,28-7,51) serta jenis kelamin (OR=2,70, 95% CI:1,11-6,64) dengan berat badan lebih, sedangkan frekuensi ke food store (total, supermarket, pasar, mini-market), frekuensi ke food service place total, rumah makan, restoran fast food), pola konsumsi sayur buah, dan sosial ekonomi responden tidak berhubungan signifi kan. Pada analisis multivariat, variabel yang mempengaruhi frekuensi datang ke pedagang kaki lima adalah frekuensi konsumsi kudapan, aktivitas fisik, jenis kelamin, dan total pengeluaran.Kesimpulan: Frekuensi datang ke pedagang kaki lima, konsumsi kudapan, aktivitas fisik, jenis kelamin, dan total pengeluaran berhubungan dengan status berat badan lebih.KATA KUNCI: food outlet, overweight, obesitas